MANAJEMEN FUND RAISING PEMBANGUNAN MASJID DI DESA PAYUDANG DUNGDANG GULUK-GULUK SUMENEP PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 9 TAHUN 1961 TENTANG PENGUMPULAN UANG ATAU BARANG - Ainurrosifi; Azizah, Ninik (Irtifaq, 2023)
This article discusses the management of finding funds for the construction of the Al-Falah mosque in Payudan Dundang village. This research is field research with a juridical-empirical approach, examining problems that exist in the field or society using legal or statutory rules. Data was collected through interviews, observation and documentation. The data obtained is processed into descriptive data which is then analyzed using Islamic Law and Law Number 9 of 1961 concerning the Collection of Money or Goods to obtain a conclusion. The results of this research show that the management of the search for funds was carried out on the highway with TOA media and a sound system as loudspeakers, and the proceeds were immediately spent the next day according to current needs. In the perspective of Islamic law, this activity means that avoiding negative impact takes priority over pursuing benefits. Meanwhile, from the perspective of Law No. 9 of 1961 concerning the Collection of Money or Goods, this activity does not comply with fund collection procedures because it does not apply for permission from the competent authorities, nor is it a mandatory order from religion and/or customary law, and because it is not carried out in a limited environment, so requires a permit as security and guarantee for these activities. Keywords: Search for funds, mosque funds, collecting money or goods.